Cooperative Principles at Work: Unveiling EFL Classroom Interaction in AKM University through a Sociopragmatic Lens - Reza Oktaviabri; Agwin Degaf (Journal of Pragmatics Research, 2023)
This research explores the collaborative nature of successful conversations between lecturers and students at AKM's English Language Center, using Hymes' SPEAKING theory to understand the social aspects involved. The study employs qualitative methods and a sociopragmatic approach to analyze the data. The findings reveal 123 instances where maxims, principles that guide effective communication, were observed. Among these, 92 instances demonstrated the fulfillment of maxims, 29 exhibited the flouting of maxims, and 2 showed a combination of flouted maxims. Importantly, participants tended to adhere to maxims more often than deviate from them. The dominant maxims observed were relevance (21%), manner (18%), and quality (16%). Conversely, 71% of instances displayed the flouting of maxims, 19% showed violations, and 10% indicated infringements. The study also highlights the social aspects represented by the SPEAKING components. These elements include the classroom setting and morning time (S), involvement of lecturers and students (P), provision of explanations and instructions (E), usage of educational language to establish familiarity (A), striking a balance between seriousness, enthusiasm, and humor (K), oral communication (I), adherence to religious and politeness norms (N), and the presence of dialogues and narratives (G). Overall, the research indicates that the effective functioning of the class can be attributed to the active participation and adherence to cooperative principles by the speech participants.